(untitled) (Palíndromo, 2017)
The exercise of writing is a challenge to the researcher and academic student, it requires reading, theoretical basis, rationale, a lonely and persevering do. The research brings discomfort, disaccommodation, sadness, requires a lot to reach the path to dialogue - document theory, explanatory affections, plausibility - powers and desires. The passion for the subject and the research object minimizes the difficulties and facilitating the exercise of writing, especially in the dissertation or thesis category. Writing is a romantic construction, a starting point, resilient and love-falling.